Notch1 Modulation of Cellular Calcium Regulates Mitochondrial Metabolism and Anti-Apoptotic Activity in T-Regulatory Cells - Saini, Neetu; Lakshminarayanan, Sowmya; Kundu, Priyanka; Sarin, Apurva (Frontiers in Immunology, 2022)
As the major hub of metabolic activity and an organelle sequestering pro-apoptogenic intermediates, mitochondria lie at the crossroads of cellular decisions of death and survival. Intracellular calcium is a key regulator of these outcomes with rapid, uncontrolled uptake into mitochondria, activating pro-apoptotic cascades that trigger cell death. Here, we show that calcium uptake and mitochondrial metabolism in murine T-regulatory cells is tuned by Notch1 activity. Based on analysis of Tregs and the HEK cell line, we present evidence that modulation of cellular calcium dynamics underpins Notch1 regulation of mitochondrial homeostasis and consequently anti-apoptotic activity. Targeted siRNA-mediated ablations reveal dependency on molecules controlling calcium release from the endoplasmic reticulum (ER) and the chaperone, glucose-regulated protein 75 (Grp75), the associated protein VDAC1 and MCU, which together facilitate ER-mitochondrial calcium transfer and uptake. Endogenous Notch1 is detected in immune-complexes with Grp75 and VDAC1. Deficits in mitochondrial oxidative and survival in Notch1 deficient Tregs, were corrected by the expression of recombinant Notch1 intracellular domain, and in part by recombinant Grp75. Thus, the modulation of calcium dynamics and consequently mitochondrial metabolism underlies Treg survival in conditions of nutrient stress. This work positions a key role for Notch1 activity in these outcomes.